2002
DOI: 10.1309/6utx-gvc0-12nd-jjeu
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus–Associated B-Cell Lymphoproliferative Disorders in Angioimmunoblastic T-Cell Lymphoma and Peripheral T-Cell Lymphoma, Unspecified

Abstract: Various patterns of Epstein-Barr virus (EBV)-associated B-cell lymphoproliferation occur in patients with immunodeficiency. We studied 17 cases of T-cell lymphoma displaying extensive EBV-driven B-cell lymphoproliferation or simultaneous/subsequent EBV-associated B-cell lymphoma. In 10 cases of angioimmunoblastic T-cell lymphoma, an uncommonly prominent population of EBV+ atypical, activated, focally confluent large transformed B cells was found in the background of T-cell lymphoma. In 4 cases, an EBV-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
157
1
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 187 publications
(170 citation statements)
references
References 26 publications
9
157
1
3
Order By: Relevance
“…Two recent studies reported the expression of IL-21 and its receptor by Hodgkin-Reed/ Sternberg cells (35,36). IL-21 could be responsible for the EBNA-2-negative, LMP-1-positive viral gene expression seen also in the EBV-positive B cell proliferations in the angioimmunoblastic T cell lymphomas (11). These malignant T cells are believed to originate from the T FH cells of GCs (37, 38), and therefore they probably produce IL-21.…”
Section: Resultsmentioning
confidence: 99%
“…Two recent studies reported the expression of IL-21 and its receptor by Hodgkin-Reed/ Sternberg cells (35,36). IL-21 could be responsible for the EBNA-2-negative, LMP-1-positive viral gene expression seen also in the EBV-positive B cell proliferations in the angioimmunoblastic T cell lymphomas (11). These malignant T cells are believed to originate from the T FH cells of GCs (37, 38), and therefore they probably produce IL-21.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that rare cases of B-cell lymphoma after angioimmunoblastic T-cell lymphoma and concurrent angioimmunoblastic T-cell lymphoma and large B-cell lymphoma have been reported. [8][9][10][11] Definitive classification of the B-cell process may be difficult, but it is most important not to overlook the underlying T-cell malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…She had previously undergone an autologous stem cell transplant. Unlike solid organ transplants these do not involve prolonged use of immunosuppressants and are not associated with EBV lymphoproliferative disorders.High rates of EBV infected lymphocytes have been reported in patients with angioimmunoblastic lymphoma [9]. At diagnosis a few patients with angioimmunoblastic lymphoma have been reported to also have a coexisting EBV lymphoproliferative disorder [9].…”
mentioning
confidence: 99%
“…High rates of EBV infected lymphocytes have been reported in patients with angioimmunoblastic lymphoma [9]. At diagnosis a few patients with angioimmunoblastic lymphoma have been reported to also have a coexisting EBV lymphoproliferative disorder [9].…”
mentioning
confidence: 99%
See 1 more Smart Citation